TRANSITIONAL JUSTICE: A CONCEPT WITH VARIOUS FACETS (Annual of the Faculty of Philosophy in Skopje, 2020)
Transitional justice is a relatively new concept, especially in academic terms; itstheoretical, research and practical fundaments are still being in a phase of embedmentbut also they are object of various controversies. This article tries to shed more light onthe paradigm of transitional justice in the context of the concepts around which it hasbeen build – and in return, which determine its essence, such as transition, law andjustice and peacebuilding in the conflict’s aftermath or the end of the authoritarian regimes.Bearing in mind the historic and political context in which the concept appearedat first, this research focuses on the etymology, the notion’s evolution, the meaning anddilemmas in implementing its key mechanisms. The article makes a critical assessmentof the expectations from the transitional justice, which are quite often unrealistic, whileit also emphasizes the fact that its mechanisms disregard the root causes and rather payattention to the ‘cure’ of the consequences of internal conflicts and authoritarian regimes.The key hypothesis is that today’s notion of transitional justice is a brainchild ofthe liberal paradigm: its utility is seen in promotion of liberal political and economicideology of liberalism rather than in providing societal conditions for durable positivepeace.
Keywords: TRANSITIONAL JUSTICE; TRANSITION; DEMOCRATIZATION; PEACEBUILDING; RULE OF LAW; LIBERALISM